THE ASSESSMENT OF THE INFLUENCE OF WOMEN'S ATTITUDES ABOUT SCREENING BENEFITS AND MOTIVATIONAL FACTORS ON THEIR PARTICIPATION IN THE PAPANICOLAU SCREENING TEST - Jovanovic, Vesna; Pazun, Vesna; Maksimovic, Vesna; Vukovic, Vesna (HEALTH CARE, 2021)
Introduction/Aim: In Serbia, cervical cancer (CC) is the second most common cancer, after breast cancer. The Papanicolaou test (PAP test) is used for the early detection of cervical cancer. Motivational factors and attitudes of women about the benefits of the Papanicolaou screening test can affect the rate of participation in it. The aim of the research was to examine whether there is a connection between women's attitudes about the benefits of screening and motivational factors and their participation in the Papanicolaou screening test of CC.Methods: This cross-sectional study included 300 women aged 21 to 69, who came for a gynecological examination to the Gynecology and Obstetrics Clinic "Narodni Front" in Belgrade, in the period from June to December 2015. Data were collected from all respondents on their demographic characteristics, reason for coming to the clinic, how often they underwent screening (Papanicolaou test), as well as data on their attitudes about the benefits of screening and motivation for undergoing the Papanicolaou screening test using a part of the questionnaire called CPC -28 questionnaire (in Spanish, Creencias, Papanicolaou, Cancer -28).Results: Of the 300 women who participated in the study, 37.3% of women regularly participated in the Papanicolaou test, 43.7% irregularly, and 19.0% never. Women who participated regularly in screening were significantly more likely to believe that it was important to have a regular Pap test to know they were healthy (F = 13.59; p˂0.001) and that the Pap test was the best way to determine early-stage CC (F = 12.29; p˂0.001) compared to women who were irregular and who had never participated in screening. Women who participated irregularly or who had never participated in the screening program would be motivated to participate in it significantly more often if someone developed CC in their family or environment (F = 5.11; p = 0.007), while women who regularly participated would be motivated significantly more often by gynecologist’s recommendations (F = 5.58; p = 0.004) and care for their own health (F = 6.93; p = 0.001). The high level of motivation was significantly related to the decision of women to regularly participate in screening (x2 = 13.05; p = 0.001) in relation to women who were irregular or who had never participated in screening.Conclusion: Within this research, it was noticed that only every third respondent regularly underwent the Papanicolaou screening test, which is far lower than the set national goals that at least 75% of the target population of women aged 25 to 64 should be covered by organized screening. It is necessary to raise women's awareness about the importance of Papanicolaou screening for early detection of CC, as well as about all other preventive measures, and especially about the importance of the HPV vaccine.
Keywords: cervical cancer, Papanicolaou test, screening test, attitudes, motivation